2012
DOI: 10.1007/s00404-012-2287-5
|View full text |Cite
|
Sign up to set email alerts
|

Cancer during pregnancy: perinatal outcome after in utero exposure to chemotherapy

Abstract: In utero exposure to chemotherapy during the second and third trimesters of pregnancy carries minimal morbidity to the unborn fetus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 19 publications
1
14
0
1
Order By: Relevance
“…Some authors have reported that the exposure to chemotherapy during the second and third trimester is associated with low birthweight, foetal growth retardation, intrauterine death, premature births, microcephaly, mental retardation and impaired learning behaviour (Caligiuri & Mayer, ; Cardonick, Usmani, & Ghaffar, ; Zemlickis et al., ). By contrast, other authors (Abdel‐Hady et al., ) did not find any significant differences, in terms of birthweight, comparing infants born to mothers exposed to chemotherapy during pregnancy with infants born to women who did not receive chemotherapy at the same gestational ages. More recent multicentre case–control studies by Amant et al.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…Some authors have reported that the exposure to chemotherapy during the second and third trimester is associated with low birthweight, foetal growth retardation, intrauterine death, premature births, microcephaly, mental retardation and impaired learning behaviour (Caligiuri & Mayer, ; Cardonick, Usmani, & Ghaffar, ; Zemlickis et al., ). By contrast, other authors (Abdel‐Hady et al., ) did not find any significant differences, in terms of birthweight, comparing infants born to mothers exposed to chemotherapy during pregnancy with infants born to women who did not receive chemotherapy at the same gestational ages. More recent multicentre case–control studies by Amant et al.…”
Section: Introductionmentioning
confidence: 65%
“…By contrast, Abdel‐Hady et al. () comparing the birthweight of 61 infants born to mothers exposed to chemotherapy during pregnancy with that of 60 infants born to women who did not receive chemotherapy in the same gestational ages did not find any significant differences in the two groups.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Some cancer treatments, including chemotherapies with antimetabolites and alkylating agents, have known teratogenic risks to a developing fetus, ranging from spontaneous abortion to severe congenital malformations. [28–30] Another issue to consider regarding reproductive health, contraception, and cancer is the issue of risk for sexually transmitted infections (STIs) as a result of unprotected sexual activity. [31] Undergoing cancer treatment increase physiologic susceptibility for STIs due to compromised immune systems, that may in turn result in negative reproductive health outcomes associated with persistent STI.…”
Section: Issues Related To Cancer and Sexualitymentioning
confidence: 99%
“…When AML is diagnosed in the second and third trimesters, chemotherapy can be successfully administered and should start without delay as per the non‐pregnant population given that the risks of malformation are minimal and treatment delays may compromise maternal outcome without improving the outcome for the foetus. Although there are increased risks of prematurity, late miscarriage and foetal growth restriction, these are generally low (Abdel‐Hady et al , ) and delaying therapy is generally a riskier option as foetal outcomes appear good. Careful co‐ordination and good communication between the MDT and all clinical teams are paramount in planning for delivery between chemotherapy cycles to avoid neutropenic phases.…”
mentioning
confidence: 99%